(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Acute pancreatitis (AP) is the inflammatory condition of the pancreas characterized by clinical manifestations of epigastric pain, digestive turbulence, tachycardia, fever, peritonitis and respiratory distress. The pathophysiological hallmark of acute pancreatitis was activation of the trypsin, release of pro-inflammatory mediators and organs damage. Therefore, this retrospective cohort was conducted to determine the outcome of AP in ICU patients by retrieving medical records of AK-diagnosed patients at the ICU of Allied Hospital, Faisalabad (2017-22). Fifty-eight patients, including 35 females and 23 men, diagnosed with AP were incorporated in the study. The clinical and pathological investigations were traced, computed tomography and Ranson scoring system for the determination of the severity of AP was used. Of these, 19 patients died during their stay at hospital but significantly high (p<0.05) proportion of individuals recovered. Their mean hospital stay was 7.20+3.44, while admission to ICU lasted 2 to 8 days with a mean of 4.89+2.86. A sum of 35 (60.34%) participants were female, whereas 23 (39.65%) were male out of which 13 females and 6 males died. Hemoglobin, white blood cell, and platelet counts of survivors were greater than (p<0.05) non-survivors, 9.12+3.72, 17.78+6.17, 3.4+0.71 and 7.89+2.87, 14.32+6.01, and 2.3+0.45, respectively. In contrast, the hematocrit and blood urea nitrogen levels of deceased were significantly (p<0.05) higher (41+9.44, 44.11+17.08 and 36+9.18, 28.01+9.78, respectively). Biochemical analysis revealed that serum albumin, liver enzymes, serum creatinine, lactate, lipase and total bilirubin values were high in non-survivors (p<0.05) than survivors i.e. 3.4+1.2, 141+48, 2.9+0.65, 588+220, 1012+566, 2.2+0.91 and 3.2+0.87, 106+32, 2.1+0.77, 411+189, 867+332, 1.8+0.34, respectively. Hence, it was concluded that biochemical investigation like BUN, amylase and creatinine had the efficacy in predicting prognosis and severity of the disease and gallstones were the foremost cause of the presented AP patients.